MOTIVASI FILIPINA MELAKUKAN KERJASAMA PERTAHANAN DAN KEAMANAN DENGAN AMERIKA SERIKAT DALAM ENHANCED DEFENSE COOPERATION AGREEMENT (EDCA) TAHUN 2014 - Shindy Apvionita Ebri; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is the study of diplomacy and strategy analyzes about motivation Philippines conduct defense and security cooperation with the United States in the Enhanced Defense Cooperation Agreement (EDCA) in 2014. This research used qualitative methods which is done by explaining the case based on existing facts. The techniques used to collects data to study the case to library research in the form of journals, books, report and website. The theoretical framework applied in this research are neorealism perspective, national interest concept from Hans J. Morgenthau, nation-state analysis level and decision making theory from Richard C. Snyder. This research is motivated Philippines conduct defense and security cooperation with the United States in the Enhanced Defense Cooperation Agreement (EDCA) on 28th April 2014 because internal and external conditions of the Philippines confront of disputes South China Sea. The dispute dealing with one of the great strength in Asia namely Tiongkok. The Philippines considers Tiongkok military strength from year to year has increased and Tiongkok strengthening its military presence to occupy more islands the disputed Spratly Island in the Philippines. Forms of this cooperation is the Philippines offered military bases to the United States, joint military exercises, maritime patrol by the United States and modernizing the armed forces of the Philippines.Keywords: Enhanced Defense Cooperation Agreement (EDCA), Philippines, United States.